Finite element modelling of the static and dynamic impact behaviour of thermoplastic composite sandwich structures - Brown, Kevin Anthony (2007)
The overall objective of this study was to develop and validate a predictive modelling methodology for simulating the static and dynamic impact failure response of thermoplastic composite sandwich structures. The work has primarily focused on sandwich constructions with commingled woven fabric glass/polypropylene composite skins and a crushable polypropylene foam core.